How Consumers Respond to Embarrassing Service Encounters: A Dehumanization Perspective - Sun, Yixia; Wang, Xuehua; Hoegg, JoAndrea; Dahl, Darren W. (Journal of Marketing Research, 2023)
The current research advances understanding of how consumers respond to embarrassing service encounters. Across a combination of field and online studies, the authors provide evidence that (1) consumers prefer self-service to human services when purchasing embarrassing products or services; (2) when self-service is not available, consumers respond more positively to a mechanistic service provider than to a personable service provider; and (3) if consumers must engage in embarrassing social interactions, they dehumanize service providers, perceiving them as more mechanistic and less capable of emotional reactions than when engaging in nonembarrassing service interactions. The authors also examine consumers’ familiarity with the service provider as a boundary condition for the effect. Collectively, the results provide converging evidence for the proposed framework and have substantive implications for service management.